Does surgical approach or prosthesis type affect hip joint loading one year after surgery? - Wesseling, Mariska; Meyer, Christophe; Corten, Kristoff; Simon, Jean-Pierre; Desloovere, Kaat; Jonkers, Ilse (Gait & posture, 2016)
•Differences in hip loading during gait between surgical procedures.•Hip loading during stair ascent and descent in patients and controls.•The magnitude of hip loading is decreased in patients compared to controls in gait.•No differences between surgical procedures in hip loading.•Hip loading magnitude in stair climbing did not distinguish better compared to gait. Several approaches may be used for hip replacement surgery either in combination with conventional total hip arthroplasty (THA) or resurfacing hip arthroplasty (RHA). This study investigates the differences in hip loading during gait one year or more after surgery in three cohorts presenting different surgical procedures, more specific RHA placed using the direct lateral (RHA-DLA, n=8) and posterolateral (RHA-PLA, n=14) approach as well as THA placed using the direct anterior (THA-DAA, n=12) approach. For the DAA and control subjects, hip loading was also evaluated during stair ascent and descent to evaluate whether these motions can better discriminate between patients and controls compared to gait. Musculoskeletal modelling in OpenSim was used to calculate in vivo joint loading. Results showed that for all operated patients, regardless the surgical procedure, hip loading was decreased compared to control subjects, while no differences were found between patient groups. This indicates that THA via DAA results in similar hip loading as a RHA via DLA or PLA. Stair climbing did not result in more distinct differences in hip contact force magnitude between patients and controls, although differences in orientation were more distinct. However, patients after hip surgery did adjust their motion pattern to decrease the magnitude of loading on the hip joint compared to control subjects.